Localization of Narrow Bipolar Events over Sumatra Island Based on VHF Interferometer and Magnetic Direction Finder Systems - Edris M.Z.B.; Ahmad M.R.; Hashim N.M.Z.; Baharin S.A.S.; Salim S.I.; Ibrahim M.B.M.; Baharuddin M.Z.; Takayanagi Y.; Akita M.; Morimoto T.; Kawasaki Z. (VDE Verlag GmbH, 2025)
Narrow bipolar events (NBEs) generate strong radio emissions. In this paper, spatio-temporal analysis of 15 NBEs recorded from a tropical storm over Sumatra Island is presented. Two localization systems, namely the magnetic direction finder (MDF) and interferometer (ITF), were employed and utilized to get 2D mapping of the analysed NBEs. A total of four positive NBEs (+NBEs) and 11 negative NBEs (-NBEs) have been identified. The emission heights for +NBEs ranged from 8.38 km to 13.21 km, while for -NBEs, the emission heights were localized and compact ranging between 15.43 km and 15.76 km. The emission distances for all NBEs fell within the range of 233.33 km to 243.87 km. The maximum cloud top height was estimated at 18.61 km. The upward movement of very high frequency (VHF) radiation sources has been observed for all four positive NBEs indicating fast negative breakdowns (FNBs). ? 2024 IEEE, ? VDE VERLAG GMBH Berlin Offenbach.